Answer:
x=4
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
24−4x=2x
24+−4x=2x
−4x+24=2x
Step 2: Subtract 2x from both sides.
−4x+24−2x=2x−2x
−6x+24=0
Step 3: Subtract 24 from both sides.
−6x+24−24=0−24
−6x=−24
Step 4: Divide both sides by -6.
−6x
/−6 =
−24
/−6
x=4
Answer:
Step-by-step explanation:
4/18×2/92
=1/9×1/23
=1/207
1/9×3/63
=1/3×1/23
=1/69
12/14×1/84
=1/14×1/7
=1/98
1/7×5/65
=1/7×1/13
=1/91
17/20×1/61
=17/1220
4 1/4 ×3 1/22
=17/4×67/22
=1,139/88
=12 83/88
3 5/6×4 1/23
=23/6×93/23
=93/6
=15 3/6
=15 1/2
2 1/2×4 7/84
=5/2×343/84
=1715/168
=10 35/168
I have answered more than 2 from each set
B.t<span>he polygon is equiangular but not equilateral. this should be correct </span>
You could use 4(division) sign 25 + 3 (division sign) 15 * 10, ok?
![- x + 1 = 4x - 14 \\ - x - 4x = - 14 - 1 \\ - 5x = - 15 \\ x = 3](https://tex.z-dn.net/?f=%20-%20x%20%2B%201%20%3D%204x%20-%2014%20%5C%5C%20%20-%20x%20-%204x%20%3D%20%20-%2014%20-%201%20%5C%5C%20%20-%205x%20%3D%20%20-%2015%20%5C%5C%20x%20%3D%203)
Substitute x = 3 in any given equations. I will do in y = - x + 1
![y = - x + 1 \\ y = - 3 + 1 \\ y = - 2](https://tex.z-dn.net/?f=y%20%3D%20%20-%20x%20%2B%201%20%5C%5C%20y%20%3D%20%20-%203%20%2B%201%20%5C%5C%20y%20%3D%20%20-%202)
Therefore the answer is (3,-2)